Strategi Komunikasi Pemasaran Jawa Pos Radar Kudus Biro Jepara dalam Menarik Minat Pemasang Iklan: Strategi Komunikasi Pemasaran Jawa Pos Radar Kudus Biro Jepara dalam Menarik Minat Pemasang Iklan - khoirul muslimin; Nanik Cahya Nandy (Jurnal Komunikasi Korporasi dan Media (JASIMA), 2020)
The purpose of the study was to determine the marketing communication strategy carried out by the Jawa Pos Radar Kudus Bureau of Jepara in attracting advertising interest and to see advertising signals in the June-August 2019 period. This research is a field research (field research) descriptive qualitative research type. This study uses a cybernetics approach. This research is to find marketing communication strategies to attract advertisers in Radar Kudus, Jepara Jawa Pos Bureau, Jepara Jl Pemuda No. 90 Jepara. The data technique is carried out by observation, interviews and literature study that are relevant to the object of research and then the data is analyzed using data reduction methods, data presentation and drawing conclusions. The results of this study indicate that the marketing communication strategy of JawaPos Radar Kudus Bureau of Jepara in attracting advertising marketing interest through (1) advertising; (2) personal selling; (3) sales promotion; (4) public relations; (5) direct marketing. Of the five elements, the Jepara Jawa Pos Bureau Radar Kudus applies the theory of Integrated Marketing Communication.